ANALISIS PENGELOLAAN KOMUNIKASI KRISIS: STUDI KASUS PENANGANAN PANDEMIK COVID 19 OLEH PEMERINTAH PROVINSI SULAWESI TENGAH - Edwan; Nurhaidar (KINESIK, 2021)
The spread of the Corona Virus (covid 19) in Indonesia is increasing. Throughout 2020 the number of confirmed positive increases every day to reach hundreds of thousands of people. In Central Sulawesi, the number of confirmed positive fluctuates so that it becomes a serious concern for local governments. In a crisis situation, the provincial government has also taken a number of steps in terms of handling covid 19, especially in minimizing public concerns and anxiety in dealing with the Covid 19 pandemic. Crisis communication facing the Covid-1 pandemic in 2020. At the beginning of the emergence of Covid 19. The results of this study indicate that the Public Relations of Central Sulawesi Province has done a number of things, especially in the pre-crisis, during the crisis and a number of planning steps in the post-crisis. Several steps were taken in accordance with the technical guidelines of the central government and adapted to regional conditions and situations because they do not yet have a standard crisis planning model